Design and Implementation of Asterisk-Based VoIP Server with Top-Down Method - Mukti Mukarom, Roihan; Ahmad Jakaria, Deni (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
Asterisk is one of the most popular and versatile open-source VoIP platforms. This research aims to design and implement Asterisk-based VoIP server services using a top down method approach. The top down approach starts from planning and designing the entire system before proceeding to the detailed implementation stage. The first step involves identifying the organization's communication needs and determining the technical specifications required to meet those needs. Next, hardware and software selection, network topology, and basic configuration of the Asterisk server are carried out. After the system architecture is determined, the implementation stage is carried out by installing and configuring the Asterisk server according to the design that has been created. The configuration process includes setting up communication protocols, setting extensions, system testing is carried out to ensure that all functions run well and meet user needs. The results of this research show that the top down method is effective in building Asterisk-based VoIP server services that are reliable and suit organizational needs. The system built is capable of providing good sound quality and ease of management. Asterisk-based VoIP implementations also offer significant cost savings compared to traditional telecommunications systems.